The Cognitive Profile of Mild Cognitive Impairment Due to Dementia With Lewy Bodies—An Updated Review - Hemminghyth, Mathilde Suhr; Chwiszczuk, Luiza Jadwiga; Rongve, Arvid; Breitve, Monica Haraldseid (Frontiers in Aging Neuroscience, 2020)
Objective: Dementia with Lewy Bodies (DLB) is the second most common type of neurodegenerative dementia. Yet, the domain-specific cognitive impairment of the mild cognitive impairment (MCI) phase of this disease (DLB-MCI) is still not been established. This article gives an updated review on the neuropsychological profile of DLB-MCI, building on the findings from Ciafone et. al. (2020). Methods: We performed systematic review and searched five different electronic databases (Scopus, Cochrane, EMBASE, MEDLINE and PsycINFO) in May 2020 based on a PICO scheme. Our search was then restricted to articles published in 2019 and 2020. Ending up with a total of 90 articles to be reviewed by abstract and/or full text. Results: In total four papers were included, whereof only one met our full inclusion criteria. Despite a substantial heterogeneity, our findings indicates that DLB-MCI patients have a pattern of executive, visuospatial and attentional deficits. Conclusion: The findings indicate that the neuropsychological profile of DLB-MCI, is characterized by executive, visuospatial and attentional deficits. Furthermore, the shortage of studies clearly underlines the paucity of published research into DLB-MCI and emphasize the need for well-controlled studies.